Amphibian Taxonomic and Functional Diversity in a Heterogeneous Landscape of West-Central Mexico - Verónica Carolina Rosas-Espinoza; Karen Elizabeth Peña-Joya; Eliza Álvarez-Grzybowska; Arquímedes Alfredo Godoy-González; Ana Luisa Santiago-Pérez; Fabián Alejandro Rodríguez-Zaragoza (Diversity, 2022)
Land use in Mexico has dramatically changed in recent decades since deforested lands have been repurposed for agriculture. We evaluated the amphibian taxonomic and functional diversity of a heterogeneous landscape with ten land cover/use types in west-central Mexico. Taxonomic diversity was evaluated with q-order indices, and functional diversity was calculated with three multivariate functional diversity indices by land cover/use. The relationship between amphibian diversity, habitat structure, and environmental variables was analyzed using multidimensional distance-based analyses. Our results showed that most native land cover types exhibited a similar species richness (low values) among the studied crops, except for the riparian habitat surrounded by tropical dry forest (high richness) and secondary vegetation (intermediate richness). Regarding functional diversity, the riparian habitat surrounded by tropical dry forest, sugar cane field, and secondary vegetation had the highest values. The secondary vegetation had more functional groups than other land cover/use types. Despite the lack of a clear spatial pattern of amphibian taxonomic and functional diversity, we determined that attributes such as herbaceous cover and water availability are essential to maintain both facets with high amphibian diversity in the land cover/use types (e.g., secondary vegetation and sugar cane).